Consumer Adoption of Drone Technology for Indoor Mobility Applications - Sunkara, Gopalakrishna (Global journal of Business and Integral Security, 2025)
This dissertation investigates the consumer adoption of indoor drone technology in environments such as warehouses, hospitals, and retail spaces. It identifies the key drivers and barriers to adoption, focusing on factors such as perceived usefulness, perceived ease of use, and safety concerns using the Technology Acceptance Model (TAM) as the theoretical framework. The study employs a mixed-methods approach, incorporating a quantitative survey and qualitative interviews to gather data from a diverse range of participants across various sectors. The results highlight that perceived efficiency, cost reduction, and safety features are significant influences on the willingness to adopt indoor drones, while privacy concerns and technological trust pose barriers. Additionally, demographic factors such as age and exposure to technology play critical roles in shaping consumer attitudes. The findings provide valuable insights into the opportunities and challenges of integrating drones into indoor environments, offering practical recommendations for businesses and policymakers aiming to facilitate drone adoption. This research enhances the understanding of consumer behavior toward emerging technologies and lays the groundwork for future innovations in drone-based indoor mobility solutions.